Staffing, activities, and infrastructure in 96 specialised adult congenital heart disease clinics in Europe. (1st October 2019) - Thomet, Corina; Moons, Philip; Budts, Werner; De Backer, Julie; Chessa, Massimo; Diller, Gerhard; Eicken, Andreas; Gabriel, Harald; Gallego, Pastora; Giamberti, Alessandro; Roos-Hesselink, Jolien; Swan, Lorna; et al.
Abstract: Background: Clinical guidelines emphasise the need for specialised adult congenital heart disease (ACHD) programmes. In 2014, the working group on Grown-up Congenital Heart Disease of the European Society of Cardiology (ESC) published recommendations on the organisation of specialised care for ACHD. To appraise the extent to which these recommendations were being implemented throughout Europe, we assessed the number of patients in active follow-up and available staff resources in European ACHD programmes. Methods: We conducted a descriptive, cross-sectional, paper-based survey of specialised ACHD centres in Europe in late 2017 concerning their centre status in 2016. Data from 96 ACHD centres were analysed. We categorised ACHD programmes into seven different centre types based on their staff resources and composition of interdisciplinary teams. Results: Only four centres fulfilled all medical and non-medical staffing requirements of the ESC recommendations. Although 60% of the centres offered all forms of medical care, they had incomplete non-medical resources (i.e., specialised nurses, social workers, or psychologists). The participating centres had 226, 506 ACHD patients in active follow-up, with a median of 1500 patients per centre (IQR: 800-3400). Six per cent of the patients were followed up in a centre that lacked a CHD surgeon or congenital interventional cardiologist. Conclusions: A minority of European ACHD centres have the full recommended staff resources available. This suggests that as of 2016 either ACHD care in Europe was still not optimally organised, or that the latest ESC recommendations were not fully implemented in clinical practice. Highlights: Overview of the structure and staffing of ACHD centres in Europe. Steady increase in the number of centres but not in patient numbers per centre. High variability within centres between patient load and staff resources. Poor adherence in staff resources to the current recommendations.